n+12=6n

Simple and best practice solution for n+12=6n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n+12=6n equation:


Simplifying
n + 12 = 6n

Reorder the terms:
12 + n = 6n

Solving
12 + n = 6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6n' to each side of the equation.
12 + n + -6n = 6n + -6n

Combine like terms: n + -6n = -5n
12 + -5n = 6n + -6n

Combine like terms: 6n + -6n = 0
12 + -5n = 0

Add '-12' to each side of the equation.
12 + -12 + -5n = 0 + -12

Combine like terms: 12 + -12 = 0
0 + -5n = 0 + -12
-5n = 0 + -12

Combine like terms: 0 + -12 = -12
-5n = -12

Divide each side by '-5'.
n = 2.4

Simplifying
n = 2.4

See similar equations:

| 5(3a-1)-2(3a+2)=3(a+2+v) | | 8ln(x)-6ln(x)=ln(4x+12) | | x+2x+x+2x=140000 | | 3m+3=-12 | | c^2=b^2+c^2-100c+2500 | | 20=2(1+3x) | | 0=b^2-100c+2500 | | 8ln(x)-ln(x^6)=ln(4x+12) | | 3xsquared+2x+4=0 | | 10=6a+4-9a-a | | 3x-5=5y | | 5x-5=13-1x | | 12y-8=-10 | | 5(-3y+4)=-85 | | 5(-3+4)=-85 | | x^2+60x-10000=0 | | y=3E-13x^8 | | 2x+0=24 | | (6+3)+2= | | .5h=1.28571428571429 | | 3(2t-5)=33 | | (4-w)(4w-9)=0 | | 2y-x=5+2x | | 4s+2+7=19+10 | | (k+4)(k+1)=10 | | .3x-.5=3.7 | | 3x+3=-45 | | -15(4w-5)=-105 | | 14y=7x+28 | | x(56-2x)= | | 3w^2+13w+4=0 | | 12v+12-8v=40 |

Equations solver categories